Islamic Ethics in Public Relations - Haque, Md Shahidul (Zes Rokman Resources, 2016)
Ethics is very important in human life. Ethical practice in public relations is crucial to protect the rights of stakeholders, to gain the trust and to build the reputation of any organization. Particularly, the practice of Islamic ethics in public relations can ensure the benefits of the organizations and the public. The Almighty God guided us to all the ethics we need to practice in every sphere of our life. He mentioned the ethical guidelines for public relations in the Quran. He taught the Prophets to practice proper public relations for da’wah activities. It is divine command ethics revealed by the God. It does not depend on the standards and norms of a particular time, place or society. The main objective of this paper is to identify Islamic ethics in public relations based on the messages of the Holy Quran and Hadiths. The implication of this study will be useful to the PR practitioners of different Muslim countries and enable them to better understand the practice of Islamic ethics in Public relations.